1991
DOI: 10.1021/bi00239a007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of kinetic constants for peptidyl prolyl cis-trans isomerases by an improved spectrophotometric assay

Abstract: The kinetic properties and substrate specificity of two well-characterized peptidyl prolyl cis-trans isomerases (PPIases), cyclophilin and the FK-506 binding protein (FKBP), have been previously examined [Fischer, G., Bang, H., Berger, E., & Schellenberger, A. (1984) Biochim. Biophys. Acta 791, 87-97; Harrison, R.K., & Stein, R.L. (1990) Biochemistry 29, 1684-1689; Albers, M.W., Walsh, C.T., & Schreiber, S. L. (1990) J. Org. Chem. 55, 4984-4986]. The chymotrypsin-coupled enzymatic assay employed in these studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
481
0
10

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 528 publications
(532 citation statements)
references
References 34 publications
(44 reference statements)
34
481
0
10
Order By: Relevance
“…The identification of the Pr55gag/Cyp18 interaction by these techniques established a quite high binding affinity of the proteins to each other. This finding is at variance with the high K,n values that could be separately determined, in part, for cis and trans oligopeptide substrates covering either the millimolar range for trans isomers or slightly lower for the cis peptides [19,34]. Attempts to saturate partially Cypl8 in the enzyme catalyzed refolding of denatured RNase TI were also unsuccessful even at the highest protein concentrations used [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the Pr55gag/Cyp18 interaction by these techniques established a quite high binding affinity of the proteins to each other. This finding is at variance with the high K,n values that could be separately determined, in part, for cis and trans oligopeptide substrates covering either the millimolar range for trans isomers or slightly lower for the cis peptides [19,34]. Attempts to saturate partially Cypl8 in the enzyme catalyzed refolding of denatured RNase TI were also unsuccessful even at the highest protein concentrations used [35].…”
Section: Discussionmentioning
confidence: 99%
“…The steady-state parameters became available by the improved protease coupled assay devised by Kofron et al [19]. The measurements were performed by monitoring the absorbance of released 4-nitroaniline at 390 nm (e = 11 814 M -1 cm -1) on a Hewlett Packard 8452A diode array spectrophotometer according to Schutkowski et al [20].…”
Section: Determination Of the Steady-state Parameters Kc~t And Km Of mentioning
confidence: 99%
“…During isomerization, the C-terminus of the peptide bond is free to rotate, whereas the N-terminus of the bond remains bound at the catalytic site of the enzyme (9). The authors also concluded that R55 is the key player in cis-trans isomerization, which is supported by mutational studies (9,10). Zhao and co-workers proposed the involvement of the guanidino group of the sidechain of R55 in hydrogen bonding with the prolyl nitrogen of the substrate.…”
Section: Introductionmentioning
confidence: 92%
“…Several efforts to understand the cis-trans isomerization of the peptidyl-prolyl bond have been made using different approaches such as NMR line-shape analysis, monitoring changes in R 2 upon substrate binding, crystal structure studies with different peptides, molecular dynamics simulations, and density functional theory calculations (9)(10)(11)(12)(13). Eisenmesser and co-workers proposed that the cis conformer of the peptide interacts with residues A101, N102, A103, K82, and R55 of the enzyme; afterward, the enzyme catalyzes rotation of the peptide-prolyl bond by 180 to produce the trans conformation and makes contacts around residues L98 and S99.…”
Section: Introductionmentioning
confidence: 99%
“…CyP possesses enzymatic activity for cis-trans isomerization of peptidyl-prolyl bonds and may catalyze protein folding (Fischer et al, 1989;Takahashi et al, 1989;Schonbrunner et a]., 1991). CsA is a potent inhibitor (Kj = lop9 to M) of the PPIase activity of CyP (Kofron et al, 1991). Although attention Abbreviations: hCyPA, human cyclophilin A; CyP, cyclophilin; CsA, cyclosporin A; PPIase, cis-trans peptidyl-prolyl isomerase; FKBP, FK506 binding protein; NFAT, nuclear factor from activated T-cells; IL, interleukin.…”
mentioning
confidence: 99%